2011
DOI: 10.3748/wjg.v17.i5.578
|View full text |Cite
|
Sign up to set email alerts
|

Role of the endothelium in inflammatory bowel diseases

Abstract: Inflammatory bowel diseases (IBD) are a complex group of diseases involving alterations in mucosal immunity and gastrointestinal physiology during both initiation and progressive phases of the disease. At the core of these alterations are endothelial cells, whose continual adjustments in structure and function coordinate vascular supply, immune cell emigration, and regulation of the tissue environment. Expansion of the endothelium in IBD (angiogenesis), mediated by inflammatory growth factors, cytokines and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
140
1
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 231 publications
2
140
1
7
Order By: Relevance
“…Chronic inflammation is characterised by a shift in the type of cells present at the site of inflammation, such as a predomination of lymphocytes and macrophages [6]. Chronic inflammation may ultimately lead to tissue destruction and cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is characterised by a shift in the type of cells present at the site of inflammation, such as a predomination of lymphocytes and macrophages [6]. Chronic inflammation may ultimately lead to tissue destruction and cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies have also detected the alterations in serum levels of angiogenesis-regulating peptides following anti-TNF-α therapy. [48][49][50] Moreover, we have demonstrated that initial serum levels of vascular endothelial growth factor (VEGF) in patients with CD may be of predictive value for response to anti-TNF-α treatment. 50 In this respect, Rutella et al 51 have analyzed the release of VEGF by cultured mucosal extracts obtained from patients with CD before and after IFX administration, as well as by cultured human intestinal fibroblasts stimulated with TNF-α in the presence or absence of IFX.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we have highlighted some recruitment of proinflammatory cells from bloodstream to the site of disease. 48 Moreover, vascular endothelial cells (ECs) serve as a potent source of cytokines engaged in a complex crosstalk between innate and adaptive immunity in the intestines. 48,49 It has been shown that anti-TNF-α agents have a significant impact on these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ezek az enzimek által termelt NO gyulladáscsökkentő hatást fejt ki, ugyanis gátolja a leukociták kitapadását az endotélhez, értágító hatású és szabályozza az endotél permeabilitását. Paradox módon a leukocitákban található iNOS a gyulladásos reakciókhoz járul hozzá, míg az endotél sejtekben lévő NOS feltehetően gyulladáscsökkentő (Cromer, Mathis et al 2011, Danese 2011) (3.ábra).…”
Section: Nos Izoformák a Béltraktusbanunclassified